FAKTOR YANG BERHUBUNGAN DENGAN BERSIHAN JALAN NAPAS PADA PASIEN DENGAN GENERAL ANASTESI DI RUANG RECOVERY - Hery Kristyanta; Widyaningsih Widyaningsih; Fhandy Aldy Mandaty (LPPM STIKES Muhammadiyah Kendal, 2023)
General anesthesia (GA) is an agent used to relieve pain during surgery. Some patients after receiving general anesthesia experience ineffective airway clearance. Ineffective airway clearance in patients under general anesthesia is related to the patient's internal condition before surgery. The purpose of this study is to determine the relationship between smoking, alcohol consumption, congenital lung disease, and age with ineffective airway clearance in patients with GA in the recovery room. This study used a cross-sectional design. The number of samples used was 52 patients using purposive sampling. The instrument used is an observation sheet to identify factors of congenital lung disease, smoking, alcohol consumption, and age. Data analysis using chi-square. The results showed that there was a relationship between congenital lung disease, smoking, alcohol consumption, and age with ineffective airway clearance in patients with general anesthesia in the recovery room, respectively p=0.002, p=0.001, p=0.011, p=0.007. The factors associated with ineffective airway clearance in postoperative patients under general anesthesia include congenital lung disease, smoking, alcohol consumption, and age.